Learning from Chernobyl to tackle the Covid-19 Pandemic - Bursztyn, Marcel; Litre, Gabriela; Mesquita, Patrícia; Saito, Carlos Hiroo (Sustainability in Debate, 2021)
Learning from Chernobyl to tackle the Covid-19 pandemic